2017
DOI: 10.3390/genes8040109
|View full text |Cite
|
Sign up to set email alerts
|

Development of 44 Novel Polymorphic SSR Markers for Determination of Shiitake Mushroom (Lentinula edodes) Cultivars

Abstract: The shiitake mushroom (Lentinula edodes) is one of the most popular edible mushrooms in the world and has attracted attention for its value in medicinal and pharmacological uses. With recent advanced research and techniques, the agricultural cultivation of the shiitake mushroom has been greatly increased, especially in East Asia. Additionally, demand for the development of new cultivars with good agricultural traits has been greatly enhanced, but the development processes are complicated and more challenging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
17
2
Order By: Relevance
“…This set of eight markers could differentiate among 20 L. edodes cultivars, with PIC values ranging from 0.269 to 0.764, with an average of 0.409 ( Table 2). Novel SSR markers for L. edodes were previously described by Lee et al [7] and Moon et al [8]. Lee et al [7] reported that the PIC values of 44 SSR markers with dinucleotide to pentanucleotide repeats ranged from 0.10 to 0.89, with an average of 0.511 and Moon et al [8] determined that the PIC values of 16 SSR markers with dinucleotide and trinucleotide repeats were between 0.07 and 0.89, with an average of 0.612.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This set of eight markers could differentiate among 20 L. edodes cultivars, with PIC values ranging from 0.269 to 0.764, with an average of 0.409 ( Table 2). Novel SSR markers for L. edodes were previously described by Lee et al [7] and Moon et al [8]. Lee et al [7] reported that the PIC values of 44 SSR markers with dinucleotide to pentanucleotide repeats ranged from 0.10 to 0.89, with an average of 0.511 and Moon et al [8] determined that the PIC values of 16 SSR markers with dinucleotide and trinucleotide repeats were between 0.07 and 0.89, with an average of 0.612.…”
Section: Discussionmentioning
confidence: 99%
“…Novel SSR markers for L. edodes were previously described by Lee et al [7] and Moon et al [8]. Lee et al [7] reported that the PIC values of 44 SSR markers with dinucleotide to pentanucleotide repeats ranged from 0.10 to 0.89, with an average of 0.511 and Moon et al [8] determined that the PIC values of 16 SSR markers with dinucleotide and trinucleotide repeats were between 0.07 and 0.89, with an average of 0.612. Our markers with tetranucleotide to hexanucleotide repeats were less useful for identifying individuals compared with the markers mainly comprising dinucleotide repeats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological properties of medicinal mushrooms are largely conferred by secondary metabolites; these metabolites have received intense research attention [1,49,53]. Here, we used antiSMASH to search for gene clusters encoding secondary metabolites in G. incarnatum [38].…”
Section: Secondary Metabolites and Terpene Pathwaymentioning
confidence: 99%
“…In addition, the proteomes of C. protrusum, E. weberi, T. reesei, T. virens, M. grisea, and Aspergillus nidulans were clustered into orthologous groups using OrthoFinder [52]. The multiple sequence alignments of the single-copy orthologs was used for phylogenetic analysis using the Neighbor-Joining method, which was conducted in MEGAX, to validate the relationships among C. protrusum and the other three fungi in the family Hypocreaceae [53].…”
Section: Orthologous Gene Families and Phylogenomic Analysismentioning
confidence: 99%